MEMBANGUN KEMANDIRIAN SISWA: TITIK SEMU KONSEP MERDEKA BELAJAR DAN PRINSIP PENDIDIKAN ISLAM - Amalia Soleha; Milati Nuril Azka; Imron Sahroni; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
This study critically examines the concept of student independence within the Merdeka Belajar curriculum and identifies the potential emergence of a “pseudo-independence” when independence is interpreted merely as technical freedom without a strong value-based foundation. The research employs a qualitative library research method using content analysis and critical analysis of educational policy documents, Islamic education literature, and previous studies. The findings indicate that independence in Merdeka Belajar is largely oriented toward learning autonomy and self-regulated learning; however, in practice, it may be distorted when detached from moral and spiritual orientation. This condition produces pseudo-independence characterized by confusion in direction, external influence dominance, and pragmatic tendencies in learning processes. The study further reveals that Islamic Education provides a corrective framework through the concepts of taklif, istikhlaf, adab, and the integration of reason and revelation, positioning independence as a form of accountability before Allah. Therefore, the integration of Islamic educational values serves as a crucial foundation for reconstructing student independence so that it is not only academically autonomous but also morally and spiritually grounded.